Optical Coherence Tomography Angiography in iIchemic Retinal and Optic Nerve diseases, with Emerging Applications in Athletes - Czudowska, Michalina; Borychowska, Emilia; Zawadzka, Magdalena; Marszałek, Dominika; Kurzątkowska, Klaudia; Bystros, Aleksandra Natalia; Drozdowska, Marta; Ocimek, Aleksandra; Gwóźdź, Karolina; Mierzejewska, Zofia Aneta (Quality in Sport, 2025)
Background. Optical coherence tomography angiography (OCT-A) provides non-invasive, high-resolution assessment of retinal and optic nerve microvasculature. Ischemic disorders such as DR, DMI, RVO, RAO and NAION show characteristic microvascular deficits measurable with OCT-A biomarkers. Early data also demonstrate exercise-related modulation of retinal perfusion. Aim. To review diagnostic, prognostic and emerging exercise-related applications of OCT-A in ischemic ocular disease. Methods. Systematic overview of 30 studies evaluating OCT-A biomarkers, perfusion deficits, structure–function relationships and exercise-induced microvascular responses. Results. OCT-A reliably detects early ischemic changes—reduced vessel density, deep plexus dropout, parafoveal non-perfusion and FAZ enlargement—correlating with functional loss. It differentiates ischemic from non-ischemic RVO, maps RAO perfusion deficits and identifies radial peripapillary capillary loss in NAION. Subclinical abnormalities appear in systemic conditions. In active individuals and endurance athletes, OCT-A captures transient and training-related perfusion changes. Limitations include artifacts, segmentation errors and lack of leakage detection. Conclusions. OCT-A is essential for detecting and monitoring ischemic retinal and optic nerve disease. Key biomarkers (VD, PD, FAZ, NPA) reflect severity and prognosis. Early evidence suggests additional utility in assessing physiological microvascular adaptation to exercise.